KESENJANGAN PERTUMBUHAN EKONOMI DI PROVINSI MALUKU - Zakarias . Lamere; Jen . Tatuh; Gene G. H, Kapantow (AGRI-SOSIOEKONOMI, 2016)
This research is belongs to execute economic growth place clasification in Regency/City of Moluccas Province and to analysis economic imbalance in Moluccas Province. Analysis methood in this research use Klassen Typology, Williamson Index and Panel Data. Klassen Typology Analysis are use to vote the clasification of economic growth in every regency/city at Moluccas Provincy. Williamson Index Analysis are use to count economic imbalance rate in Moluccas Provincy. Panel Data is a bundle or a collected from time series (2006 - 2010) and data cross section (11 Regency/City), use to see many factors that made imbalance development in Moluccas Province. Klassen Typology Analysis research shown that just one area where looking forward and growth, it is Ambon City. Category area where looking suppressed in the develop process is Tual City, and prosperous area where are in down is Aru Regency, Centre Moluccas Regency, East Seram Regency, West Seram Regency, South Buru regency, S.W Moluccas Regency, S.E.W Moluccas Regency, Buru Regency, and South East Moluccas Regency. For Moluccas Province, Williamson Index in 2006 – 2010 scored at a stretch is 0, 5833; 0, 5660; 0, 6294; 0, 5883; 0, 5286. It indicates that there is a high imbalance of economic growth. Outcome panel data analysis shown that imbalance development that rate by IPM showed α = 5 percent in real by economic growth, work force growth, long road regency and real in α = 10 percent by long road province. To anticipate the imbalance in Moluccas Province that must have work force quality, high performance, and usefull for upgrading income per capita and economic growth, and so centre of economic growth must be explore to every regency/city so that economic activity not constructed at one area.